PENGARUH JAM KERJA DAN PENGALAMAN KERJA TERHADAP PRODUKTIVITAS DAN PENDAPATAN TENAGA KERJA WANITA INDUSTRI BATU BATA DI DESA TULIKUP GIANYAR - Purnami, Sang Ayu Putu Ratih; Urmila Dewi, Made Heny (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 9 No 11 (2020): VOL 9 NO 11, NOVEMBER 2020 (2390 - 2617), 2020)
Tulikup Village is one of the villages in Gianyar Subdistrict, Gianyar Regency where most of the women work in the informal sector. The informal employment sector occupied by women in Tulikup Village is a worker in the red brick industry. The purpose of this study is (1) to analyze the effect of working hours and work experience on the productivity of women workers in the brick industry in the Tulikup village of Gianyar, (2) analyzing the effect of working hours, work experience, and productivity on women's labor income in the stone industry brick in the Gianik Tulikup Village, and (3) analyze the indirect effect of working hours and work experience, on the income of women workers through productivity in the brick industry in Tulikup Gianyar Village. The sample in the study amounted to 106 female workers who were determined by the proportional random sampling method. The analysis technique used is path analysis (path analysis).. The results show that (1) working hours and work experience have a significant positive effect on the productivity of women workers in the brick industry in Tulikup Village, Gianyar Regency. (2) working hours, work experience, and productivity have a significant positive effect on women's labor income in the brick industry in Tulikup Village, Gianyar Regency. (3) working hours and work experience indirectly influence the income of women workers in the brick industry in Tulikup Village, Gianyar Regency through productivity in the form of partial mediation. Keywords : Working Hours, Work Experience, Productivity, Income